Overfat Adults and Children in Developed Countries: The Public Health Importance of Identifying Excess Body Fat - Maffetone, Philip B.; Rivera-Dominguez, Ivan; Laursen, Paul B. (Frontiers in Public Health, 2017)
The global overfat pandemic is a serious public health crisis that places a substantial burden on economic resources in developed countries. The term overfat refers to the presence of excess body fat that can impair health, even for normal weight non-obese individuals. Excess body fat is associated with cardiometabolic dysfunction, a clinical situation that can progressively worsen, potentially leading to various common disease risk factors, chronic diseases, increased morbidity and mortality, and reduced quality of life. The prevalence of overfat populations in 30 of the world’s most developed countries is substantially higher than recent global estimations, with the largest growth due to a relatively recent increased number of people with excess abdominal fat. Abdominal overfat is the most unhealthful form of this condition, so it is concerning that average waist circumference measures, generally indicative of abdominal overfat, have increased. Despite a leveling off appearance of being overweight and/or obese in some developed countries, the overfat pandemic continues to grow.